Desarrollo de un sistema para geolocalización de ganado bovino en los páramos de Cotopaxi utilizando software y hardware libre. - Molina Molina, Danilo Paul (2020)
The present research consisted in the development of a web system for cattle monitoring at Juan Montalvo parish of Latacunga city that visualizes in real time the cattle location, for this was necessary to use Open Source tools such as PHP and MySql In addition, a GPS prototype was developed that emits bovine coordinates, this prototype was designed with Arduino modules and renewable energy, which is responsible to send: longitude, latitude, time and date to a web server for subsequent data manipulation. The iterative-incremental model was applied which allowed to develop the system through iterations. Research methods and techniques were used, such as: observation, expert’s criteria and the interview, which helped to know the needs, with system functionalities, resulting in a finished deliverable prototype, where cattlemen carried out the prototype tests. The purpose of this research was to provide security and protection to the livestock population through free software and hardware, in this way the proposed objectives at the beginning of the investigation were met.